RAD51 genotype and triple-negative breast cancer (TNBC) risk in Polish women - Smolarz, Beata; Zadrożny, Marek; Duda-Szymańska, Joanna; Makowska, Marianna; Samulak, Dariusz; Michalska, Magdalena M.; Mojs, Ewa; Bryś, Magdalena; Forma, Ewa; Romanowicz-Makowska, Hanna (Polish Journal of Pathology, 2013)
The most lethal damage for the cell among all damage is double-strand breaks (DSB) of DNA. DSB cause development of cancer diseases including the triple-negative molecular subtype of breast cancer. The aim of this work was to evaluate the single nucleotide polymorphism -135G>C (rs1801320) of the RAD51 gene encoding DNA repair proteins by homologous recombination (HR) in triple-negative breast cancer (TNBC). We assessed the RAD51 -135G>C polymorphism in 50 women with triple-negative breast cancer and in 50 women from the control group. RAD51 polymorphism was analysed by the PCR-RFLP (restriction fragment length polymorphism) technique. Our results demonstrated a significant positive association between the RAD51 C/C genotype and TNBC, with an adjusted odds ratio (OR) of 5.95 (p = 0.002). The homozygous C/C genotype was found in 68% of breast cancer cases and 20% of controls. The variant 135C allele of RAD51 increased TNBC risk. This is the first study linking single nucleotide polymorphisms of the RAD51 gene with TNBC incidence in the population of Polish women. In conclusion, RAD51 polymorphisms may be regarded as predictive factors of triple-negative breast cancer in the female population. Large studies are needed to confirm our findings.